Occupational accidents at a coal mine Waterberg District in Limpopo Province - Dama, Tshimangadzo Joseph (My University, 2021)
The coal mining industry is reported to be the most dangerous workplace in the world. Most of the mine workers working in underground coal mines as well as open cast mines are exposed to occupational accidents which result in injuries or death of workers, decrease in production and increasing financial expenditure. Occupational accidents are defined as unplanned occurrences often resulting in personal injuries, damage to machines, tools and equipment, and the halting of production. The most common causes of occupational accidents in coal mines are natural causes, unsafe acts in the workplace, inadequate health and safety training, workplace hazards, dust explosions, landslips, technical failures related to transport, human error and rock fall. It has been reported that there are more than 350,000 workplace fatalities and more than 270 million injuries annually worldwide. Objectives The objectives of this study were to determine types of health and safety training offered to mineworkers and find out types of mine hazards at a coal mine in Waterberg District of Limpopo Province. Methods A quantitative descriptive cross-sectional method was used in the study. The population comprised 800 mineworkers who worked at Exxaro Grootegeluk Coal Mine. Simple random sampling was used to select 286 mineworkers who participated in the study. A self-administered questionnaire was used to collect data. Statistical analysis and descriptive statistics were used to analyse data. Results The study findings show that the majority of mine workers at 24% who worked at the coal mine in Waterberg District in Limpopo Province were between the ages of 26 and 30 years, followed by 59 or 21% of those between the ages of 31 to 35. 107(37%) had work experience of between 2 to 4 years and 124(43,4%) completed grade 12. 95% of them received training in hazards identification while 97% know how to identify hazards in the workplace. The study further found that majority of the mine workers or vi 93% agree that they work in a dusty place, but are provided with dust masks. 99% agree that they always put on personal protective equipment before starting work. 97% agree that they are provided with correct personal protective equipment to perform their daily tasks. Conclusion The study concluded that mine workers who worked at Exxaro Grootegeluk Coal Mine are provided with health and safety related training and with correct personal protective equipment to perform their daily tasks. Keywords Coal mine, occupational accidents, occupational injuries and mine workers, health and safety training and personal protective equipment.
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Coal mine; Health and safety training and personal protective equipment; Occupational injuries and mine workers; Industrial accidents -- Reporting; Hand injuries -- therapy; Occupational mortality -- South Africa -- Statistics